Changes in monetary regimes and the identification of monetary policy shocks: Narrative evidence from Canada - Julien Champagne; Rodrigo Sekkel (Bank of Canada, 2017)
We use narrative evidence along with a novel database of real-time data and forecasts from the Bank of Canada's staff economic projections from 1974 to 2015 to construct a new measure of monetary policy shocks and estimate the effects of monetary policy in Canada. We show that it is crucial to take into account the break in the conduct of monetary policy caused by the announcement of inflation targeting in 1991 when estimating the effects of monetary policy. For instance, we find that a 100-basis-point increase in our new shock series leads to a 1.0 per cent decrease in real GDP and a 0.4 per cent fall in the price level, while not accounting for the break leads to a permanent decrease in real GDP and a price puzzle. Finally, we compare our results with updated narrative evidence for the U.S. and the U.K. and argue that taking into account changes in the conduct of monetary policy in these countries also yields significantly different effects of monetary policy.
Keywords: E31; E32; E43; E52; E58; 330; Business fluctuations and cycles; Central bank research; Econometric andstatistical methods; exchange rate regimes; inflation and prices; inflation targets; interest rates; monetary policy; monetary policy framework